Enucleolation of porcine oocytes - Fulka, J; Moor, R M; Loi, P; Fulka, J (Theriogenology, 2003)
Germinal vesicles (GVs) in immature mammalian oocytes contain prominent nucleoli whose role in the process of oocyte maturation is not fully understood. Here we report that the microsurgical removal of nucleoli from immature fully grown porcine oocytes permits germinal vesicle breakdown and chromosome condensation and the enucleolated oocytes mature up to the second metaphase. Interestingly, the enucleolation of growing oocytes which, although unable to mature, resulted in germinal vesicle breakdown and the formation of a cluster of condensed chromatin. These results indicate that the nucleolus in fully grown oocytes is dispensable at least for nuclear maturation. On the other hand, the results obtained in growing oocytes suggest the role of the nucleolus in the cell cycle regulation.
Keywords: prasata; Swine; viabilita buněk; Suction; oocyty; Metaphase; mikrochirurgie; Cell Nucleolus; Cell Survival; odsávání; buněčné dělení; chromatin; Chromatin; kultivované buňky; Animals; Cell Division; ženské pohlaví; Microsurgery; zvířata; metafáze; Cells, Cultured; Female; buněčné jadérko; Oocytes